Total Ankle Arthroplasty is Associated with Decreased Risk of Postoperative Total Knee Arthroplasty Compared to Ankle Arthrodesis - Gloria Coden MD; Andrzej Brzezinski MD; Kurt Hofmann MD (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis Introduction/Purpose: There is a known association between ankle arthritis and ipsilateral knee arthritis. However, it is unknown if the increased range of motion and improved gait mechanics provided by total ankle arthroplasty (TAA) may delay the progression of knee arthritis compared to ankle arthrodesis (AA). We hypothesized that patients treated with TAA would have a lower incidence and longer time to total knee arthroplasty (TKA) compared to AA. Methods: We retrospectively reviewed a matched cohort of 5726 AA and 5726 TAA performed between 1/1/2007 and 12/31/2021 using a commercial claims database. Patients with a history of preoperative ipsilateral or unknown laterality TKA were excluded. Records were reviewed for demographics, comorbidities, diagnosis, documented history of an ankle deformity, and postoperative ipsilateral or unknown laterality TKA. Mahalanobis nearest neighbor matching was performed based on age, gender, year of surgery, geographical region, and diagnosis was used to determine the cohorts from 13,679 AAs and 5726 TAAs. Mean follow-up was 2.2 years. Univariate and multivariate analyses were performed to assess for risk factors. Significance was set at p< 0.05. Results: Patients who underwent TAA were older (p < 0.001), female (p < 0.001), had earlier ankle surgery (p < 0.001), and increased ankle deformity (p < 0.001) than AA, but rates of rheumatoid arthritis (p=0.54) and posttraumatic arthritis (p=0.53) compared to osteoarthritis were similar. Patients who underwent AA were 2.77 times more likely to undergo a postoperative TKA compared to TAA (p < 0.001). However, for those who underwent a TKA, patients with an AA (mean=3.48 years) tended to wait longer before proceeding with TKA than patients who underwent TAA (mean=2.62 years, p< 0.001). Risk factors for undergoing postoperative TKA included having AA (p < 0.001), earlier year of ankle surgery (p < 0.001), older age (p < 0.001), lack of ankle deformity (p < 0.005), lack of obesity (p < 0.047), and posttraumatic arthritis (p < 0.001), while gender (p=0.55) and rheumatoid arthritis (p=0.75) were not. Conclusion: Our results showed that there is a significantly higher incidence of patients undergoing TKA after AA compared to TAA (p < 0.001). Therefore, we recommend that surgeons consider TAA over AA, especially in young, active patients with minimal knee arthritis as a strategy to help delay the progression of knee arthritis. Patients who underwent AA tended to have a longer time interval to TKA (p < 0.001), which may be related to the longer expected recovery from an AA compared to TAA. With improved rehabilitation protocols for TAA, patients may recover faster so that they can proceed with their ipsilateral TKA earlier.